LAGU SEBAGAI MEDIA PEMBELAJARAN TATA BAHASA ARAB (NAHWU) - Purwanto, Nanang Joko (Maharaat: Jurnal Pendidikan Bahasa Arab, 2018)
Arabic as an international language is very important to be learned. In the process of learning, some people experience various obstacles. One of the obstacles occurs during learning Arabic grammar (nahwu). At this point, some people can overcome that obstacles, and some others not. Therefore, it needs a breakthrough for teacher to choose the right learning media so that the learning process will be easier and more fun. Learning media has an important role in learning process because the difficult material and the long time needed to learn can be easier and not boring to be learned if it is chosen correctly. Among those learning media, one of learning media that can be used is song. By using a song as learning media, it is easier for students to memorize the lyric in spite of using foreign language. Furthermore, the words and sentences within the song explains the meaning and structure in Arabic sentence rule. Hence, the song can be chosen as Arabic learning media in learning Nahwu course. Several songs that can be used are â€œKasih Ibuâ€ and â€œDua Mata Sayaâ€ in Arabic Language.Â  Â Â